2003
DOI: 10.1002/nau.10153
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle strength and response to pelvic floor muscle training for stress urinary incontinence

Abstract: There was a positive relation between both pelvic floor muscle strength increase and maximal strength, and improvement of stress urinary incontinence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(61 citation statements)
references
References 26 publications
2
57
0
2
Order By: Relevance
“…These findings confirm the results reported by Bø (2003), who found a positive association between the increase of PFM strength demonstrated by perineometric measurements and improvement in stress incontinence.…”
Section: Discussionsupporting
confidence: 95%
“…These findings confirm the results reported by Bø (2003), who found a positive association between the increase of PFM strength demonstrated by perineometric measurements and improvement in stress incontinence.…”
Section: Discussionsupporting
confidence: 95%
“…However, any positive effect of such treatment may be mediated by changes in the contractility and/or bulk of the urethral rhabdosphincter rather than of the levator ani. While the effect of pelvic floor muscle exercises (PFMC) on intravaginal pressures and muscle bulk of the levator ani can be determined relatively easily [24,25] and while such changes are associated with treatment response, it is not clear whether such changes are the cause of clinical improvement or just a marker for improvements in urethral structure and/or function.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Many randomized controlled trials and systematic reviews have shown that PFM training is effective for treating stress urinary incontinence, with success rates of between 44% and 80% among adult females. 8,9 However, there is little evidence that it can improve pelvic organ prolapse and its symptoms. 10 Some theories have been proposed in order to explain the mechanism of action of PFM training in pelvic organ prolapse.…”
Section: Introductionmentioning
confidence: 99%